Tratamento de efluente lácteo por reação foto-fenton seguido de eletrocoagulação - Braun, Luana (2018)
This paper presents a study of the treatment of dairy effluent from photo-Fenton (UV/H2O2/Fe2+) and electrocoagulation processes, aiming to obtain physico-chemical parameters below the standard values for disposal in water bodies according to environmental legislation. From a small number of assays the maximization region of experimental responses was reached to removal of Chemical Oxygen Demand (COD), Total Organic Carbon (TOC) and iron remaining in the solution (Fe2+), using a experiments called Box-Behnken Design (BBD) that enables the application of the response surface methodology. A total of 48 assays were carried out to in the treatment of dairy effluent. Among these, in the treatment of effluent by photo-Fenton reaction, 17 planned assays (BBD 33) were carried out to determine the maximization region of both COD and TOC responses; followed by 3 independent assays for the certification of experimental conditions for surface maximization of both responses. Then, for the treatment of the effluent by electrocoagulation, another 17 planned assays (BBD 33) were performed, with 2 more independent assays. In the combination of both processes, 7 assays were performed (BBD 32), in addition to 2 independent assays. The best conditions of the photo-Fenton process provided the removal rates: 61% COD and 72% TOC; while the electrocoagulation process resulted in: 51% and 20% for COD and TOC, respectively. The application of the electrocoagulation after the photo-Fenton process resulted in the removal of 92% COD (170 mg L-1) and 88% TOC (72 mg L-1), also assuring values of other physicochemical parameters within the limits of discarding established by the environmental legislations. The disposal of the effluent treated by the combination of both processes is environmentally safe, since bioassays of acute toxicity by Artemia salina indicated their low toxicity.